All Roof, No Wall: Peter Boston, A-Frames and the Primitive Hut in Twentieth-Century British Architecture, c. 1890–1970. (2019) - McKellar, Elizabeth
Abstract: A very particular type of modern house in Britain — A-frames of the 1950s and 1960s — emerged from a much longer history of British and Scandinavian-German primitivism centred on the cruck-frame. This article focuses on a small number of architect-designed examples and introduces one of the main proponents of the type, Peter Boston (1918–99). The tension between the A-frame's familiarity as a universal dwelling type and its adoption as a signifier of modernity is a central theme. In the British twentieth-century context, the 'modern' included a strong vernacular element, and the new A-frames, which formed part of the 'timber revival' of the 1950s and 1960s, were informed by a long-standing interest in the history of cruck-framed construction from the Arts and Crafts onwards, which in turn was part of a wider pan-north European building culture.